Education on the Qur'anic Concept of Ulama to Enhance Community Islamic Literacy - Said Usman Umar; Mardan Mardan; Muhsin Muhsin (Maslahah: Jurnal Pengabdian Masyarakat, 2026)
This Community Partnership Program (PKM) aims to enhance public understanding and awareness of the concept of ulama from the Qur'anic perspective and to strengthen its implementation in the development of Islamic education and character education. The program was carried out using a participatory educational approach that included lectures, interactive discussions, the study of Qur'anic verses concerning ulama, and mentoring sessions to help participants identify the values of leadership, integrity, and scholarly responsibility that can be applied in daily life and educational practices. The program materials focused on the concept of ulama based on Qur'an Surah Ash-Shu'ara (26):197 and Surah Fatir (35):28, along with relevant hadiths, and their implications for the development of educators, learners, and the wider community. The results of the program indicate an improvement in participants' understanding of the characteristics of ulama as described in the Qur'an, namely individuals who possess sound knowledge, piety, integrity, and a strong commitment to conveying the truth responsibly. Furthermore, participants gained greater awareness of the importance of integrating Qur'anic values into educational practices through character development, ethical leadership, and lifelong learning. This program contributes to strengthening Islamic literacy within the community while encouraging the implementation of the values exemplified by ulama in the development of Islamic education that emphasizes character formation and moral development in both educational institutions and society.